Peran Penanggung Jawab Program Sks Dalam Manajemen Kurikulum 2013 Berbasis Sistem Kredit Semester Di Mtsn 3 Nganjuk - Ira Nurjayanti (ICO EDUSHA, 2023)
In the education segment, Indonesia continues to strive to develop and improve the curriculum in order to achieve the educational goals of the Gold Generation. The 2013 curriculum is almost evenly applied to all levels of education units in Indonesia, some institutions apply it with certain systems such as the Semester Credit System (SKS). The general characteristic of the 2013 Curriculum is that educational goals focus on learning outcomes, while credits are a tactic to achieve these goals. Unfortunately, behind the luck of the SKS applied at MTsN 3 Nganjuk, there is a role in charge of the SKS Program which has not been much highlighted. This research is entitled "The Role of Person in Charge of the Credit Program in Curriculum Management 2013 Based on Semester Credit System at MTsN 3 Nganjuk". With the aim of the study to describe the role and implications of the role of the Person in Charge of the Credit Program in Curriculum Management 2013 Based on the Semester Credit System at MTsN 3 Nganjuk. This research uses qualitative research methods or field research (field research). Primary data and secondary data are the data sources used. The result of this research is that the person in charge of the SKS Program acts as a planner, organizer, implementer, and supervisor. In addition, the role of the person in charge of the SKS Program has good implications for both Human and Non-Human at MTsN 3 Nganjuk. Keywords: Role, Curriculum Management, Semester Credit System. REFERENSI Arumsari, Nurul Rizka. 2017.Penerapan Planning, Organizing, Actuanting, dan Controling di UPTD DIKPORA Kecamatan Jepara. Jurnal Ekonomi dan Bisnis Kontempoter, 3 (2) : 3 http://jurnal.unpand.ac.id/index.php/EBK/article/view/873 diakses tanggal 13 April 2022 Departemen Agama RI. 2012. Al-Quran dan Terjemahannya. Cet. X; Bandung: CV Diponegoro : 250. Dokumen Panduan Penyelenggaraan Sistem Kredit Semester di Madrasah Negeri 3 Nganjuk Tahun 2019 Meilianawati, Try. 2016. Peran Wakil Kepala Kurikulum Dalam Pelaksanaan Administrasi Kurikulum di Madrasah. Skripsi di Publikasi. Kudus : Sekolah Tinggi Agama Islam Negeri Kudus, 2016 : 23 http://eprints.stainkudus.ac.id/432/5/05.%20BAB%20II.pdf diakses tanggal 13 April 2022 Muhlis, Ahcmad. 2017. Pengembangan Pembelajaran Dengan Sistem Kredit Semester di MTS Negeri Sumber Bungur Pamekasan, Nuansa, 14 (1) : 146 http://ejournal.iainmadura.ac.id/index.php/nuansa/article/view/1317/941 diakses tanggal 18 April 2022 Rostika, Desi, Wildan Zakaria. 2016. Analisis Implementasi Kurikulum 2013 Dengan sistem kredit semester. Manajemen Pendidikan 25 (2) : 194 http://anzwild.com/wp-content/uploads/2017/03/2016-sep.pdf diakses tanggal 11 Mei 2022 Rusman. 2009. Manajemen Kurikulum. Jakarta : Raja Grafindo Persada Sidiq,Umar, Moh, Miftachul Coiri. 2019. Metode Penelitian Kualitatif Di Bidang Pendidikan, Ponorogo : Nata Karya http://repository.iainponorogo.ac.id/484/ diakses tanggal 4 April 2022 Sintasari, Beny, Nuzulul Fitria. 2021. Manajemen Kurikulum Berbasis Madrasah di MTs Barhrul Ulum Gadingmangu Perak Jombang. Urwatul Wutsqo, 10 (2) : 207 https://www.jurnal.stituwjombang.ac.id/index.php/UrwatulWutsqo/article/view/291 diakses tangal 28 April 2022 Soetjito dan Raflis Kosasi. 2011. Profesi Keguruan. Jakarta : PT Rineka Cipta Syarafuddin, Amiruddin. 2017. Manajemen Kurikulum. Medan: Perdana Publishing Aksara Oemar Hamalik. 2006. Manajemen Pengembangan Kurikulum. Bandung: PT Remaja Rosdakarya Wahid, Abdurrahman. 2016 . Penerapan Sistem Kredit Semester (SKS) Pendidikan Agama Islamdi SMA Muhammadiyah 3 Jakarta. Jurnal Pendidikan Islam, 7 (2) : 23 https://journal.uhamka.ac.id/index.php/jpi/article/view/176/133 diakses tanggal 16 April 2022